IoT-based prototype for water quality monitoring and control - Fitri, Eliya; Ranuharja, Fadhli (Journal of Industrial Automation and Electrical Engineering, 2025)
Clean water quality is an important factor for public health, but the problem of inconsistent PDAM water quality in Sijantang Koto village is still an obstacle. This research aims to design and build a prototype of an Internet of Things (IoT)-based water quality monitoring and control system. The system uses pH sensors and TDS sensors to measure water quality parameters in real-time. The data from the sensors is processed by the ESP32 microcontroller and displayed through LCD and Blynk application for remote monitoring. In addition to the monitoring function, the system is also equipped with an automatic control mechanism using a pump to add purifying agent (PAC) and pH neutralizer (CaCo3) when the water parameters are outside the standard threshold. The results show that the system is able to detect changes in water quality and automatically control water parameters according to the set standards. The implementation of this system is expected to increase public awareness of the quality of water used and provide solutions in a more efficient and modern clean water management.